Analisis Budaya K3 dengan Nordic Occupational Safety Climate Questionnaire dan Safety Culture Maturity Model - Afifah, Alidina Nur; Hadi, Suseno (Universitas Ahmad Dahlan, 2018)
Background: Implementation and good practice of Occupational Health and Safety (OHS) based on state regulation should be sufficient for a company to promote safety culture. However, âZero Accidentâ as its measurable goal has not been consistently achieved, thus we can deduce that OHS practice has not gained its optimum level. We need to know why this gap happens; which safety culture elements are considered as dominant obstacle and support factors at the same time. The research purpose is to measure safety culture maturity level as well as factors that influence safety culture in a company, as case study PT X. Method: As research designs, analytical descriptive and cross-sectional design using quantitative and qualitative approaches were mixed together. The research samples consisted of 96 individuals and 5 key informants. Data was gathered using NOSACQ-50 questionnaire, SCMM questionnaire, and in-depth interviews. Its independent variables were OHS priority management, commitment and competency, OHS empowering management, OHS equality management, worker commitment on OHS, priority and risk acceptance, communication in OHS practice, learning and trust between co-workers in OHS competency, confidence level on OHS system effectivity, work duration, education level, and job position, whilst the only dependent variable was safety culture maturity level. Result: The research result showed that there were correlations between all independent variables of NOSACQ-50 components and safety culture maturity level. It was also concluded that OHS priority management and commitment and competency were both considered as the most influential factors to safety culture (OR=6,29). Following up the research result, it is recommended to the company to officially state Safety Culture as OHS department vision, to improve training management especially for increasing training participation from each business unit, to educate employees to have better mindset on punishment and incident reporting activities, and to improve communication effectiveness within employees related to OHS practice. Keywords: Safety Culture, Safety Climate, Safety Culture Maturity Level, NOSACQ-50, SCMM.